The SOCIAL NETWORK ANALYSIS EFEKTIVITAS PROMOSI PARIWISATA MELALUI TAGAR #BATUKOTAWISATA DI TWITTER - Priya Falaha Muttaqien (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
The tourism sector in Indonesia has been badly affected by the covid 19 pandemic. Slowly the tourism sector is starting to revive along with the shift of covid 19 from a pandemic to an endemic one. One of the quick strategies in the revival of the tourism sector is the movement of domestic tourists to local Indonesian destinations. The movement of domestic tourists can be triggered by tourism promotions. Using the social network analysis method, this research wants to see the effectiveness of tourism promotion through the hashtag #BatuKotawisata on Twitter social media. The results of the study show that tourism promotion through the #BatuKotawisata hashtag on Twitter is not effective because the main actor spreading the hashtag is not an actor with an interest in the tourism sector. The main actor brings his own interests through the message conveyed in the hashtag #BatuKotawisata. The positive thing that can be seen in tourism promotion through the #BatuKotawisata hashtag is that this hashtag has penetrated trending topics.